2019
DOI: 10.3354/aei00321
|View full text |Cite
|
Sign up to set email alerts
|

Snorkel technology to reduce sea lice infestations: efficacy depends on salinity at the farm site, but snorkels have minimal effects on salmon production and welfare

Abstract: Sea lice are a critical health issue in most salmonid farming regions. New cage-based technologies can prevent infestations from occurring, such as the 'snorkel', which introduces an impermeable barrier that separates salmon lice Lepeophtheirus salmonis from Atlantic salmon Salmo salar in the surface waters where lice are most abundant. While snorkels provide protection from lice, their lice-reducing effect can vary under different environmental conditions. We conducted production-scale sea-cage experiments at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Brackish surface water can also reduce the efficacy of skirts and snorkels by causing both lice and salmon to reside below the level of the barrier (Oppedal et al . 2019), while there is evidence that barrier technology may reduce the performance of cleaner fish when used in combination (Gentry et al . 2020).…”
Section: What Preventative Methods Are Available?mentioning
confidence: 99%
“…Brackish surface water can also reduce the efficacy of skirts and snorkels by causing both lice and salmon to reside below the level of the barrier (Oppedal et al . 2019), while there is evidence that barrier technology may reduce the performance of cleaner fish when used in combination (Gentry et al . 2020).…”
Section: What Preventative Methods Are Available?mentioning
confidence: 99%
“…This was most pronounced in spring–summer at inner‐fjord sites, where a relatively thick, stable brackish layer accumulated (Figure 1 ). Experimental trials have shown that seasonal and spatial variation in salinity has a strong effect on the efficacy of depth‐based preventions (Geitung et al, 2019 ; Oppedal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible retaining effect by lice skirts or biofouling might be linked to the same factors that that make a lice skirt effective in shielding the salmon from copepodites. The effectiveness of the lice skirts can be reduced by environmental conditions like the presence of a cline deeper in the water than the lower edge of the lice skirt, which have been shown for the presence of a halocline (Samsing et al, 2016;Oppedal et al, 2019). We investigated the water profile for haloclines, thermoclines, and pycnoclines (only the latter is shown in this paper, because the density of seawater is a function of salinity and temperature, Helber et al, 2012); however, we found no clines for the Liceskirt7 site.…”
Section: Impact Of Retention By Lice Skirt or Biofouling On Lice Abunmentioning
confidence: 97%